If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 9 = 0 Reorder the terms: 9 + 4t = 0 Solving 9 + 4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4t = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 4t = 0 + -9 4t = 0 + -9 Combine like terms: 0 + -9 = -9 4t = -9 Divide each side by '4'. t = -2.25 Simplifying t = -2.25
| -4(5-4x)=-40+6x | | -7=a-7 | | 7(m-7)=28-4m | | 33-3n=-6(n-8) | | -17=15n-20 | | 11m+10=9m | | 60=log(x) | | 4=4x+9 | | -3(n-4)-3=3-(n+2) | | 7x+1=1+8x | | ab+5a-b-5=0 | | 18(v+3)-2v=4(4v+1)-11 | | 6/5:2,7 | | 4=p-36 | | -7+8p=-7-2p | | 8v-(8v-6)= | | -12-5y=-32 | | √25/289 | | 6x2/3x | | 5/6=1/2v | | -5-6(k+5)=-(k-5) | | 3a+7-8a= | | 6x+1=10x-1 | | 100+20(5.25)=x | | 3(w+1)=w+19 | | 6(x-1)=-3+6(x+8) | | (-4)-((-9/-9)-8) | | x^2=100-15x | | 159+12x=96-5x | | -29m=-1131 | | X-3X+4+8=X | | -40-6n=-3(8n-3) |